2001
DOI: 10.1002/1097-0142(20010601)91:11<2026::aid-cncr1228>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Expression of survivin correlates with apoptosis, proliferation, and angiogenesis during human colorectal tumorigenesis

Abstract: BACKGROUND To identify the role of survivin, a novel inhibitor of apoptosis (IAP) in colorectal tumorigenesis, the authors investigated tissue expression of survivin in human colorectal tumors including 43 hyperplastic polyps, 171 adenomas with low dysplasia, 42 adenomas with high dysplasia, and 60 carcinomas in adenoma, and examined whether the expression of survivin correlated with tumor cell apoptosis, proliferation, and angiogenesis, which is known to initiate the imbalance between cell proliferation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
207
3
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(236 citation statements)
references
References 16 publications
17
207
3
4
Order By: Relevance
“…Finally, the association between survivin, p53 and bcl-2 protein has been investigated based on the following background: (i) in the complex regulation of apoptosis and cell cycle progression, p53 and bcl-2 play a crucial role (Miyashita and Reed, 1993;Miyashita et al, 1994); (ii) wild-type p53 has been shown to negatively regulate human survivin at both mRNA and protein levels in 2774 ovarian carcinoma cells (Mirza et al, 2002), and to suppress survivin expression in lung adenocarcinoma cells (Hoffman et al, 2002); (iii) survivin expression has been associated with mutant p53 accumulation in ovarian and gastric cancer (Lu et al, 1998;Cohen et al, 2003), and during colorectal carcinogenesis (Kawasaki et al, 2001); moreover, a coassociation of survivin and bcl-2 has been found in breast and gastric cancer (Tanaka et al, 2000;Kawasaki et al, 2001). Our study, as well as other reports Cohen et al, 2003), failed to show any relationship between p53 or bcl-2 and survivin expression, suggesting that these proteins could exert their functions through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the association between survivin, p53 and bcl-2 protein has been investigated based on the following background: (i) in the complex regulation of apoptosis and cell cycle progression, p53 and bcl-2 play a crucial role (Miyashita and Reed, 1993;Miyashita et al, 1994); (ii) wild-type p53 has been shown to negatively regulate human survivin at both mRNA and protein levels in 2774 ovarian carcinoma cells (Mirza et al, 2002), and to suppress survivin expression in lung adenocarcinoma cells (Hoffman et al, 2002); (iii) survivin expression has been associated with mutant p53 accumulation in ovarian and gastric cancer (Lu et al, 1998;Cohen et al, 2003), and during colorectal carcinogenesis (Kawasaki et al, 2001); moreover, a coassociation of survivin and bcl-2 has been found in breast and gastric cancer (Tanaka et al, 2000;Kawasaki et al, 2001). Our study, as well as other reports Cohen et al, 2003), failed to show any relationship between p53 or bcl-2 and survivin expression, suggesting that these proteins could exert their functions through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cellular and viral proteins have been identi®ed that directly inhibit caspase and are referred to as the IAP family (for review, LaCasse et al, 1998). Survivin is also a member of the IAP family, and it is unique in that its expression is encountered in only dividing cells, such as tumor cells and developing cells (Ambrosini et al, 1997;Adida et al, 1998a,b;Kawasaki et al, 1998;Lu et al, 1998;Swana et al, 1999). As an IAP family member, Survivin contains a single baculovirus IAP repeat (Ambrosini et al, 1997) and interacts directly with caspase 3 (CPP32/Yama/Apopain) and 7 (Mch3, ICE-LAP3, CMH-1) in a cell free system (Tamm et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Survivin is a recently identi®ed IAP family protein (Ambrosini et al, 1997), and its expression is detected speci®cally in tumor cells (Adida et al, 1998a;Kawasaki et al, 1998;Lu et al, 1998;Swana et al, 1999) and in cells during embryonic development (Adida et al, 1998b). Compared with other IAP family members, such as crmA, p35, iap and ILP (Clem and Miller, 1994;Gagliardini et al, 1994;Miura et al, 1995;Xue and Horvitz, 1995;Duckett et al, 1996;Deveraux et al, 1997), Survivin contains a single baculovirus IAP repeat, lacks a carboxyl-terminal RING ®nger and is unique in that its expression is observed only in proliferating cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 High levels of survivin have been found in most human cancers, including cancers of the lung, colon, pancreas, prostate, breast, and stomach. [2][3][4][5] Expression of survivin has been reported to be correlated with shorter survival in patients with non-small cell lung cancer (NSCLC). 3 Survivin is expressed in the G 2 /M phase in a cell-cycleregulated manner, and its interaction with the microtubules of mitotic spindle at the beginning of mitosis is essential for its anti-apoptotic function.…”
Section: Introductionmentioning
confidence: 99%